Isolation of new Brazilian giant viruses from environmental samples using a panel of protozoa - Dornas, Fábio P.; Khalil, Jacques Y. B.; Pagnier, Isabelle; Raoult, Didier; Abrahão, Jônatas; La Scola, Bernard (Frontiers in Microbiology, 2015)
The Megavirales are a newly described order capable of infecting different types of eukaryotic hosts. For the most part, the natural host is unknown. Several methods have been used to detect these viruses, with large discrepancies between molecular methods and co-cultures. To isolate giant viruses, we propose the use of different species of amoeba as a cellular support. The aim of this work was to isolate new Brazilian giant viruses by comparing the protozoa Acanthamoeba castellanii, A. polyphaga, A. griffini and Vermamoeba vermiformis as a platform for cellular isolation using environmental samples. One hundred samples were collected from 3 different areas in September 2014 in the Pampulha lagoon of Belo Horizonte city, Minas Gerais, Brazil. PCR was used to identify the isolated viruses, along with hemacolor staining, labelling fluorescence and electron microscopy. A total of 69 viruses were isolated. The highest ratio of isolation was found in Acanthamoeba polyphaga (46.38%) and the lowest in Vermamoeba vermiformis (0%). Mimiviruses were the most frequently isolated. One Marseillevirus and one Pandoravirus were also isolated. With Brazilian environmental samples, we demonstrated the high rate of lineage A mimiviruses. This work demonstrates how these viruses survive and circulate in nature as well the differences between protozoa as a platform for cellular isolation.